Structural basis of transcription: Backtracked RNA polymerase II at 3.4 Å resolution - Wang, Dong (2009)
X-ray crystal structure determination of RNA polymerase II in the reverse translocated, or “backtracked” state completes the picture of the transcribing enzyme. The notable feature of the backtracked structure is a binding pocket for the first backtracked nucleotide, but no significant interaction with additional backtracked residues. The structure in the presence of the elongation factor TFIIS reveals a rearrangement whereby cleavage of the RNA may occur, with the release of a dinucleotide. Due to the stabilization of the one-residue-backtracked state by the polymerase, TFIIS-induced cleavage is an important, if not predominant, mechanism of proofreading in transcription.